INFLUENCE OF PROCESSING AND NON-PROCESSING SERVICE QUALITY ON PASSENGER SATISFACTION SEMARANG AIRPORT - Divanandya Zahra Ramadhana; Kurniani Kurniani; Eva Purnamasari (Applied Accounting and Management Review (AAMAR), 2023)
The purpose of this study is to investigate the variables that affect Passenger Satisfaction. The determining factors considered are the Service Quality of Processing and Non- Processing. This study uses a quantitative research method with a purposive sampling technique, namely by distributing questionnaires to air service users who depart through Semarang Airport with 100 respondents. The SPSS 26 statistical test tool is used in this data analysis procedure together with a variety of linear regression analysis techniques. The findings revealed that Passenger Satisfaction is positively and significantly impacted by the Service Quality of Processing and Non-Processing. The magnitude of the coefficient of determination is 0.660, this means that 66% of Passenger Satisfaction can be explained by the Quality of Processing and Non-Processing Services while the remaining 34% is explained by other variables not examined in this study. This shows that Processing and Non-Processing Service Quality plays an important role in increasing Passenger Satisfaction.